2008
DOI: 10.1093/intqhc/mzn005
|View full text |Cite
|
Sign up to set email alerts
|

Health sector accreditation research: a systematic review

Abstract: The health care accreditation industry appears to be purposefully moving towards constructing the evidence to ground our understanding of accreditation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
400
3
28

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 425 publications
(466 citation statements)
references
References 55 publications
24
400
3
28
Order By: Relevance
“…[23,30,31] In other systematic reviews, accreditation programs are consistently found to facilitate improvements in medical institutions and healthcare quality. [32][33][34] The standards included in this study are intended to determine whether the goals and purpose of the accreditation system are being achieved well. In the future, it will be necessary to carry out additional research to determine how accreditation affects patients' well-being as well as research to evaluate outcome indicators, and cost-effectiveness studies.…”
Section: Discussionmentioning
confidence: 99%
“…[23,30,31] In other systematic reviews, accreditation programs are consistently found to facilitate improvements in medical institutions and healthcare quality. [32][33][34] The standards included in this study are intended to determine whether the goals and purpose of the accreditation system are being achieved well. In the future, it will be necessary to carry out additional research to determine how accreditation affects patients' well-being as well as research to evaluate outcome indicators, and cost-effectiveness studies.…”
Section: Discussionmentioning
confidence: 99%
“…org). ISQua is dedicated to the health care sector, has 70 member countries (Greenfield & Braithwaite, 2008), including Denmark. While accreditation has been the national strategy for quality development in Denmark, this is not the case in the other Nordic countries and the main experience of accreditation in the Nordic countries is from Denmark (Engel & Andersen, 2017).…”
Section: Quality Development and Accreditationmentioning
confidence: 99%
“…1 A complex picture emerges from reviews of healthcare accreditation schemes worldwide but two key features are common -promoting change and professional development. 2 Accreditation in primary care settings is generally seen as a way of assessing and benchmarking the performance of general practice care across a broad range of clinical and organisational domains. 3 It describes a formal process of selfassessment and external and independent peer review to encourage best practice and can result in recommendations for continuous quality improvement of safety and quality.…”
Section: Introductionmentioning
confidence: 99%